Relación entre las formas de un verbo supletivo : el caso del gallego, comparado con el de otras lenguas iberorrománicas - Szijj, Ildikó (Acta Hispanica, 2011)
The verb ’go’ (Spanish, Portuguese, Galician ir, Catalan anar) is a suppletive verb in the Iberian romance languages. The roots and their distribution in the paradigm are similar in standard Spanish, Portuguese and Galician, but rather different in Catalan. There is a diachronic variaton and a synchronic difference between these languages in the 4th and 5th person of the present ^ indicative mood. The variants can also be observed in dialects: according to the Galician Unguistic Atlas (Atlas lingüístico galego), the root can vary in the Galician linguistic territory in the previous two forms and in the 5th person of the imperative mood. These three forms within the paradigm are related in that thy are the "truly" arhygotonic forms in the three present tenses and they have the same morphological structure.